PENGEMBANGAN INSTRUMEN KOMPETENSI PEDAGOGIK DAN KOMPETENSI KEPRIBADIAN UNTUK MENILAI KINERJA GURU MATEMATIKA SMP DI KOTA ENDE - Juwita Merdja (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2018)
This study aims to develop instruments pedagogical competence and personalcompetence to assess the performances of mathematics teachers of junior high schools (JHSs)in Ende city. The developed assessment instruments Assessment instrument is in the form of aquestionnaire. This was a research and development study employing the qualitative andquantitative approaches. The research subjects were students of JHSs in Ende city with a totalof 60 students in tryout I (small-scale tryout) and tryout II (large-scale tryout) with a total of150 students. The content validity of the instrument was assessed through expert judgmentand the construct validity through the factor analysis. The determination of the assessmentinstrument reliability coefficients was made by using Cronbach’s Alpha. The results of thestudy are as follows. 1) Instrument mathematics teacher pedagogical competence generateddeclared valid and reliable; 2) Instrument personal competence generated math teachersdeclared valid and reliable; 3) The results of the factor analysis showed that of the 20variables / items analyzed in pedagogical formed into six groups / major factor with varianceof 57.078%; 4) The results of the factor analysis showed that of the 10 variables / items areanalyzed on the competence of personality is formed into three groups / major factor withvariance of 53.354%